Determinants of Regional Housing Market in Croatia - Valerija Botriæ; Željka Kordej de Villa (European Regional Science Association (ERSA), 2005)
This paper investigates regional differences in the housing market in Croatia. Housing market in Croatia is still relatively undeveloped, but highly regionally dispersed. Regions characterized by excessive demand on the housing and real estate markets are concentrated in the capital city and recently in the tourist areas. Regions characterized by the excessive supply are those in the economically depressed areas. At the same time, Croatian labour market lacks significant geographical mobility, which contributes to the differences on the housing market as well. Croatian housing market had to experience the phase of price liberalization, as well as other markets in the transition process. This specific liberalization, though, was not considered as a priority during the process. Price developments and turnover dynamics are still bounded by underdeveloped and not updated cadastre, purchasing power of the Croatian residents, newly discovered and soon surpassed credit liabilities, and at this moment still limited possibilities of non-residents real estate purchases. Within the prospect of becoming an EU member, Croatian housing market is expected to gone through significant changes. The main purpose of our paper is to quantitatively assess the situation prior to the EU accession. We apply principles of hedonic price methods in order to estimate the determinants of housing prices, taking account of regional differences. Our database consists of the detailed spatial data. Since the database is relatively new, the time dimension of housing market developments is not assessed in this paper.
Keywords: 330